2016
DOI: 10.1017/erm.2016.12
|View full text |Cite
|
Sign up to set email alerts
|

Genome research in pre-dementia stages of Alzheimer's disease

Abstract: Genetic characterization of individuals at risk of Alzheimer's disease (AD), i.e. people having amyloid deposits in the brain without symptoms, people suffering from subjective cognitive decline (SCD) or mild cognitive impairment (MCI), has spurred the interests of researchers. However, their pre-dementia genetic profile remains mostly unexplored. In this study, we reviewed the loci related to phenotypes of AD, MCI and SCD from literature and performed the first meta-analyses evaluating the role of apolipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 142 publications
2
15
0
1
Order By: Relevance
“…Regarding APOE ε4 genotype and incident MCI, APOE ε4–positive women with SCD showed strong associations with MCI 5 years later, whereas APOE ε4–negative women with SCD did not. This is in line with the literature as APOE ε4 is a genetic risk factor for AD dementia and conversion from its earlier stages [29]. APOE ε4–positive men with SCD and especially APOE ε4–negative men with SCD showed strong associations with incident MCI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding APOE ε4 genotype and incident MCI, APOE ε4–positive women with SCD showed strong associations with MCI 5 years later, whereas APOE ε4–negative women with SCD did not. This is in line with the literature as APOE ε4 is a genetic risk factor for AD dementia and conversion from its earlier stages [29]. APOE ε4–positive men with SCD and especially APOE ε4–negative men with SCD showed strong associations with incident MCI.…”
Section: Discussionsupporting
confidence: 91%
“…with SCD did not. This is in line with the literature as APOE ε4 is a genetic risk factor for AD dementia and conversion from its earlier stages [29]. APOE ε4-positive men with SCD and especially APOE ε4-negative men with SCD showed strong associations with incident MCI.…”
Section: Discussionsupporting
confidence: 85%
“…Moreno-Grau and Ruiz [14] included 6,824 patients from 8 studies in their meta-analysis. The significant association between APOE e4 and SCD disappeared when a random model was used.…”
Section: Discussionmentioning
confidence: 99%
“…However, 2 case-control studies conducted by Verdile et al [12] and Caselli et al [13] showed that the prevalence of APOE e4 did not significantly differ between healthy controls and SCD groups. In May 2016, Moreno-Grau and Ruiz [14] reported that APOE e4 was a genetic risk factor for the development of SCD (OR 1.151 [1.015–1.304]; p  = 0.028). However, their meta-analysis included subjects with non-SCD cognitive decline, whose mean mini-mental state evaluation scores were <25 [15].…”
Section: Introductionmentioning
confidence: 99%
“…La enfermedad de Alzheimer tiene una heredabilidad estimada de alrededor del 70% (6). Hasta la fecha, más de 20 genes se han asociado con la enfermedad de Alzheimer y, de ellos, solo tres están relacionados con las formas familiares de inicio temprano de la enfermedad: APP, PSEN1 y PSEN2 (7).…”
Section: Introducción Y Justificaciónunclassified